Complexo de Edipo, hoje? - Miguelez, Nora Beatriz Susmanscky de (2007)
This thesis central subject is the validity of the Complex of Oedipus in the present. In the current psychoanalytical literature- in particular some Lacanian French authors- the insistence on the paternal function decadence and its consequences are noticeable: the incest prohibition law lacks support and consequently the oedipian normative, the classic ways of subjectivation and, eventually, culture itself would sink. There is no doubt that the patriarchate decline somewhat affects the paternal function concept. However, it does not necessary imply in the grave consequences predicted by this widespread current psychoanytical trend. In fact, this study, partially supported by Foucault´s hyphotheses, underlines that one tipe of power decays in society whenever it is displaced by another one. Therefore there would be no normative, axiological or political emptiness in the space yielded by the patriachate under extinction threat. New powers other than patriarchal, typical of disciplinary and control societies would pervade the socio-cultural environment and give support the incest prohibition law, even in the lack of the paternal-exclusive fuel. The hypothesis of this study is that the current agents of these new powers (school, enterprise, media, propaganda, etc.), would inherit the paternal power, therefore continuing to support the oedipian interdiction, which is the guarantee of the subjectivation processes and the choice of gender and pathology